Effect of Chemical Enhancers on In Vitro Release of Salbutamol Sulphate from Transdermal Patches - Budhathoki, Uttam; Thapa, Panna (Kathmandu University Journal of Science, Engineering and Technology, 2005)
The effect of combination of PG with DMSO, BC, IPM, Tween 80 and SLS on drug release rate was studied in vitro. The mechanism of drug release was also studied by using power law. Significant difference (One way ANOVA; p